Magnetic resonance enterography in pediatric celiac disease - Gonca Koc; Selim Doganay; Eylem Sevinc; Kemal Deniz; Govind Chavhan; Sureyya B. Gorkem; Neslihan Karacabey; Mehmet S. Dogan; Abdulhakim Coskun; Duran Aslan
Abstract Objective: To assess if magnetic resonance enterography is capable of showing evidence/extent of disease in pediatric patients with biopsy-proven celiac disease by comparing with a control group, and to correlate the magnetic resonance enterography findings with anti-endomysial antibody level, which is an indicator of gluten-free dietary compliance. Methods: Thirty-one pediatric patients (mean age 11.7 ± 3.1 years) with biopsy-proven celiac disease and 40 pediatric patients as a control group were recruited in the study. The magnetic resonance enterography images of both patients with celiac disease and those of the control group were evaluated by two pediatric radiologists in a blinded manner for the mucosal pattern, presence of wall thickening, luminal distention of the small bowel, and extra-intestinal findings. Patient charts were reviewed to note clinical features and laboratory findings. The histopathologic review of the duodenal biopsies was re-conducted. Results: The mean duration of the disease was 5.6 ± 1.8 years (range: 3-7.2 years). In 24 (77%) of the patients, anti-endomysial antibody levels were elevated (mean 119.2 ± 66.6 RU/mL). Magnetic resonance enterography revealed normal fold pattern in all the patients. Ten (32%) patients had enlarged mesenteric lymph nodes. Conclusion: Although a majority of the patients had elevated anti-endomysial antibody levels indicating poor dietary compliance, magnetic resonance enterography did not show any mucosal abnormality associated with the inability of magnetic resonance enterography to detect mild/early changes of celiac disease in children. Therefore, it may not be useful for the follow-up of pediatric celiac disease.